Контингент студентів середніх спеціальних педагогічних закладів у Волинській області у повоєнний час: Луцьке педагогічне училище - Галан, Ольга (My University, 2018)
Стаття присвячена дослідженню контингенту студентів середніх спеціальних педагогічних закладів Волині на прикладі Луцького педагогічно училища. Проаналізовано фактори впливу суспільно-економічних факторів на особовий склад студентів.. The article is devoted to the study of the contingent of students of secondary specialized pedagogical institutions of Volyn on the example of the Lutsk Pedagogical College. The factors of the influence of socioeconomic factors on the personal composition of students are analyzed. The historical course of events in Volyn in 1944-1954 promotes changes in all areas of life. Since April 1944 the Lutsk Pedagogical School has begun to resume its work. There were not enough teachers and students at that time. In Lutsk, students attended a pedagogical school with unfinished school education. The vast majority of students professed the Soviet ideology. But among them were Ukrainian nationalists. They were arrested for anti-Soviet speeches. Among them – well-known director Yevhen Khryniuk. Since 1944 Lutsk's pedagogical school has been renamed into a Pedagogical College, teachers of pedagogical schools become teachers of college, and pupils are students. It enhances the prestige of the school and attracts more students. On January 1, 1945, 228 students attended the correspondence department. As of November 1, 1947, there are 830 students in the secondary specialized educational institutions of Volhynia, 294 in the Lutsk Pedagogical School. The contingent of the students of the Lutsk Pedagogical College consisted of rural youth, often with incomplete education, the number of students increased with each passing year, which made it possible to fill the deficit of teaching staff in the Volyn region.
Keywords: Луцьке педагогічне училище; розвиток педагогічної освіти в післявоєнні роки; студенти Луцького педучилища; контингент студентів